Characterisation of four popular Polish hop cultivars. (13th May 2013) - Leonardi, Michele; Skomra, Urszula; Agacka, Monika; Stochmal, Anna; Ambryszewska, Katarzyna E.; Oleszek, Wieslaw; Flamini, Guido; Pistelli, Luisa
Summary: Polish cultivars of hop ( Humulus lupulus L.) are well known as aroma and bitter raw material in the brewing industry. To characterise four popular Polish hop cultivars, Lubelski (Lublin), Marynka, Sybilla and Iunga (also known as Junga), the essential oil profiles were determined by gas chromatography/flame ionisation detector (GC‐FID) and gas chromatography/chemical ionisation mass spectrometry (GC‐CIMS) and the alpha/beta acids amounts by high‐performance liquid chromatography/diode array detector (HPLC‐DAD) analysis. In addition, the multivariate statistical analysis of the volatile profiles was performed. The results obtained evidenced qualitative and quantitative differences between the four cultivars studied and the foreign hops described in the literature. Lubelski and Iunga showed the typical chemical profile of the fine‐aroma and high‐alpha cultivars, respectively. In Marynka and Sybilla, the average amounts of alpha acids were similar to the bitter hops, but with a volatile profile characteristics of the fine‐aroma and aroma cultivars respectively.